2010
DOI: 10.5713/ajas.2010.90618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mastitis on Buffalo Milk Quality

Abstract: The objectives of this study were to compare the effectiveness of different indicators of mammary inflammation in buffalo and to evaluate the association of the indicators with buffalo milk yield, composition, and rennet coagulation properties. This study was carried out at four buffalo farms in central Italy using a total of 50 lactating buffalo. Milk from each buffalo was tested at the beginning, middle, and end of lactation. To evaluate the relationship between mastitis markers and milk components, three cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
3
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 22 publications
(33 reference statements)
10
38
3
3
Order By: Relevance
“…The milk lactose per cent remained significantly higher in normal quarters and decreased significantly by 7.79% and by 9.73% during moderate and severe infection, respectively (P<0.05). Lower milk lactose observed during mastitis is in agreement with previous studies in dairy buffaloes (Bansal et al, 2007;Sharif Tripaldi et al, 2010;Hussain et al, 2012). Lower lactose content may be due to impairment of synthetic activity of mammary tissues or decomposition by leucocytes or mastitis causing pathogens or leakage from milk into blood (Hussain et al, 2012;Reis et al, 2013).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The milk lactose per cent remained significantly higher in normal quarters and decreased significantly by 7.79% and by 9.73% during moderate and severe infection, respectively (P<0.05). Lower milk lactose observed during mastitis is in agreement with previous studies in dairy buffaloes (Bansal et al, 2007;Sharif Tripaldi et al, 2010;Hussain et al, 2012). Lower lactose content may be due to impairment of synthetic activity of mammary tissues or decomposition by leucocytes or mastitis causing pathogens or leakage from milk into blood (Hussain et al, 2012;Reis et al, 2013).…”
Section: Resultssupporting
confidence: 82%
“…Lower lactose content may be due to impairment of synthetic activity of mammary tissues or decomposition by leucocytes or mastitis causing pathogens or leakage from milk into blood (Hussain et al, 2012;Reis et al, 2013). Hence, lactose could be used as an indicator due to consistent change during intramammary infections (Tripaldi et al, 2010;Reis et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tripaldi et al (2010) found an average of 80.44% for casein/protein ratio in buffalo milk; Costa et al (2014) identified an average of 79.17% (min. of 78.07 and max.…”
Section: Milk and Whey Characteristicsmentioning
confidence: 99%